2013
DOI: 10.1021/cn300227m
|View full text |Cite
|
Sign up to set email alerts
|

Selective Catecholamine Recognition with NeuroSensor 521: A Fluorescent Sensor for the Visualization of Norepinephrine in Fixed and Live Cells

Abstract: A method for the selective labeling and imaging of catecholamines in live and fixed secretory cells is reported. The method integrates a tailored approach using a novel fluorescence-based turn-on molecular sensor (NeuroSensor 521) that can exploit the high concentration of neurotransmitters and acidic environment within secretory vesicles for the selective recognition of norepinephrine and dopamine. The utility of the method was demonstrated by selectively labeling and imaging norepinephrine in secretory vesic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
83
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 80 publications
(86 citation statements)
references
References 31 publications
3
83
0
Order By: Relevance
“…More recently, we developed NeuroSensor 521 (NS521) as a turn‐on fluorescent sensor for the catecholamines norepinephrine and dopamine (Figure 2). 6…”
Section: Introductionmentioning
confidence: 99%
“…More recently, we developed NeuroSensor 521 (NS521) as a turn‐on fluorescent sensor for the catecholamines norepinephrine and dopamine (Figure 2). 6…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21][22] Some time ago, we introduced a fluorescent sensor (sensor 1, Scheme 1) for norepinephrine and dopamine by appending a phenyl boronic acid via a flexible linker to the coumarin aldehyde. [19][20][21][22] Some time ago, we introduced a fluorescent sensor (sensor 1, Scheme 1) for norepinephrine and dopamine by appending a phenyl boronic acid via a flexible linker to the coumarin aldehyde.…”
mentioning
confidence: 99%
“…We have found that aryl-substituted coumarin-aldehydes perform very well as fluorescent sensors, 22 so an ortho-phenylboronic acid was chosen for the diol-binding unit. We have found that aryl-substituted coumarin-aldehydes perform very well as fluorescent sensors, 22 so an ortho-phenylboronic acid was chosen for the diol-binding unit.…”
mentioning
confidence: 99%
“…F luorescent labelling is a powerful tool for high-sensitivity detection of biomolecular interactions [1][2][3][4][5] . In particular, fluorescence is one of the most frequently used means of evaluating ligand-analyte complex formation in homogeneous and heterogeneous assays, as transduction of the target-binding event facilitated by fluorophores enables real-time monitoring 6 .…”
mentioning
confidence: 99%